2023
DOI: 10.3390/biology12050662
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome in the Progression of NAFLD, NASH and Cirrhosis, and Its Connection with Biotics: A Bibliometric Study Using Dimensions Scientific Research Database

Abstract: There is growing evidence that gut microbiota dysbiosis is linked to the etiopathogenesis of nonalcoholic fatty liver disease (NAFLD), from the initial stage of disease until the progressive stage of nonalcoholic steatohepatitis (NASH) and the final stage of cirrhosis. Conversely, probiotics, prebiotics, and synbiotics have shown promise in restoring dysbiosis and lowering clinical indicators of disease in a number of both preclinical and clinical studies. Additionally, postbiotics and parabiotics have recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…This study has the following advantages: our study is the first to systematically and comprehensively analyze the gut microbiota of liver cirrhosis using bibliometric methods, which is different from previous studies. For example, Pezzino S et al undertook a bibliometric study on the impact of the intestinal microbiome in NAFLD/NASH, and related liver cirrhosi based on the Dimensions scientific research database ( Pezzino et al, 2023 ). Our study includes research on cirrhosis also caused by viral hepatitis, autoimmune diseases, long-term heavy alcohol consumption, obesity, cholestasis, and other causes.…”
Section: Discussionmentioning
confidence: 99%
“…This study has the following advantages: our study is the first to systematically and comprehensively analyze the gut microbiota of liver cirrhosis using bibliometric methods, which is different from previous studies. For example, Pezzino S et al undertook a bibliometric study on the impact of the intestinal microbiome in NAFLD/NASH, and related liver cirrhosi based on the Dimensions scientific research database ( Pezzino et al, 2023 ). Our study includes research on cirrhosis also caused by viral hepatitis, autoimmune diseases, long-term heavy alcohol consumption, obesity, cholestasis, and other causes.…”
Section: Discussionmentioning
confidence: 99%
“…In liver disease, FMT trials have been performed in cirrhotic and precirrhotic stages with varying levels of success (63). In precirrhotic nonalcoholic steatohepatitis, FMTs have been largely unsuccessful in meaningfully changing clinical outcomes but have been noted as safe (64). As a corollary, smaller studies showed that FMT could improve insulin resistance, which was not sustained in larger experiences (65)(66)(67)(68).…”
Section: Fecal Microbiota Transplantmentioning
confidence: 99%
“…The complex interplay within the gastrointestinal system leads to dysbiosis-an imbalance in the intestinal microbiota [5]. Various studies have suggested that individuals with NAFLD, NASH, ALD, Cirrhosis, and Hepatocellular HCC exhibit dysbiosis [6,7]. Therefore, understanding the microbiota composition and its implications in other biological and clinical aspects can advance the diagnosis and treatment of significant liver lesions [8].…”
Section: Introductionmentioning
confidence: 99%